THE MECHANISM OF FINANCIAL PROVISION OF INNOVATIVE DEVELOPMENT OF THE REGION (ON THE EXAMPLE OF IVANO-FRANKIVSK REGION) - Shchur , R. I.; Plets' , I. I.; Mykytyuk , O. V. (The actual problems of regional economy development, 2016)
At the stage of transition to innovative model of economic development an effective mechanism of financial provision of innovative development is extremely important and indispensable catalyst of innovative processes. The article focuses on the study of the components of the mechanism of financial provision of innovative development of regions. Іnvestigated the dynamics of sources of innovative financing in Ivano-Frankivsk region. Researched features in the financial provision of innovative development of the Subcarpathian area at the expense of own and budgetary funds, loans and external financing. Identified the lack of public sources, credit funds of financing of innovations, or even their absence, in the Ivano-Frankivsk region, even though innovative capacity, it occupies a leading position among all regions of the country. The article reflects the problems of tax stimulation of innovative processes in the region and the state as a whole. Proposed to increase public provision in the investigated area and improve the tax incentives for innovative development. JEL: R 58